Isolated torsion of paraovarian cyst: a case report with review of literature - Hota, Basanta M.; Bakshi, Kavitha; Pandiri, Teja R.; Yallamandla, Devisri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Paraovarian cyst (POC) develops in the mesosalpinx, between the fallopian tube and the ipsilateral ovary. The incidence is 02-03% of adnexal masses and torsion occurs in about 01% of acute abdomen in women with adnexal mass. It is common in reproductive age and originates from the mesothelium or the embryonic remnant of Müllerian or Wolffian duct. The cyst is usually benign, unilateral, sessile, unilocular, small size and asymptomatic. The patient may be asymptomatic or present with chronic pain when a POC increases in size or with an acute abdomen when it develops complications like torsion, hemorrhage, rupture, or malignancy. Diagnosis is difficult, and surgical exploration is the gold standard for diagnosis and management. We present a case of 24-year-old unmarried girl with dull pain abdomen off and-on-and low back pain for three months is more so for last 3 days without gastrointestinal or urinary symptoms or menstrual abnormality. Infective origin was excluded clinically and on blood count. Ultrasound revealed a cystic lesion in the left adnexa likely to be a simple ovarian cyst. She developed acute abdomen features later, and laparoscopy revealed a torsion left POC of 10×10 cm. De-torsion and cystectomy were performed, and histopathology reported a benign POC of paramesonephric origin. Rare incidence and challenging diagnosis must be kept in mind in acute abdomen with adnexal mass, and surgical exploration should not be delayed. The presentation aims to report the rare pathology and Laparoscopy as the gold standard for diagnosis and management.